The Eminence of Incubation in Creative Procces As The Basic Reason of Recreation Space Development at Work - Diena Yudiarti; Hani Amelia (Balong International Journal of Design, 2019)
Creative People are known to be different in their perceptions and interpretations of their work problems, depending on the characteristics of the current situation occur (Dorst Cross, 2001). The creative process that people usually see cannot be seized by any methodology, but the creative people actually implement different types of methods. Methods have flexibility in processes, actions, and appreciations (Roozenburg Dorst, 1998; Stempfle Badke-Schaub, 2002). Creative people usually have unique characteristics while doing their job. They need some supportive situations or environments to embrace the imagination as they create an idea of the creative process. Sometimes, the ideas come out in unexpected situations, either in a relaxed situation or under pressure situations. The second stage of creative thinking from the four stages presented by Graham Wallas (1926) is the Incubation Stage which becomes the focus of this research. The need for the incubation stage will be used as one of the variables of the user aspect approach for leisure facility design which is the output expectation from this research for the recommendation of designing the facility in a Co-Working Space.